2015
DOI: 10.1186/s13014-015-0349-0
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-125 seed brachytherapy for early stage prostate cancer: a single-institution review

Abstract: PurposeWe are reporting the five-year biochemical control, toxicity profile and dosimetric parameters using iodine-125 low dose rate brachytherapy (BT) as monotherapy for early stage prostate cancer at a single institution.Material and methodsBetween April 2006 and December 2010, 169 men with early stage prostate cancer were treated with BT. Biochemical failure was defined using the Phoenix definition (nadir + 2 ng/mL). Treatment-related morbidities, including urinary, rectal and sexual function, were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 48 publications
0
16
0
2
Order By: Relevance
“…As an internal RT, iodine-125 seed implantation has been successfully used to treat a series of malignant tumors, such as prostate cancer, 24 brain tumors, 25 , 26 pancreatic cancer, 27 skin cancer, 28 ovarian cancer, 29 recurrent cervical cancer, 30 and head and neck neoplasms, 31 especially in NSCLC. Santos et al indicated that the use of iodine-125 brachytherapy after sublobar resection significantly improved local control compared with sublobar resection alone (18.6 vs 2%; P <0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…As an internal RT, iodine-125 seed implantation has been successfully used to treat a series of malignant tumors, such as prostate cancer, 24 brain tumors, 25 , 26 pancreatic cancer, 27 skin cancer, 28 ovarian cancer, 29 recurrent cervical cancer, 30 and head and neck neoplasms, 31 especially in NSCLC. Santos et al indicated that the use of iodine-125 brachytherapy after sublobar resection significantly improved local control compared with sublobar resection alone (18.6 vs 2%; P <0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, RIS implantation brachytherapy has been successfully used to treat diverse kinds of malignant tumors (17,(23)(24)(25)(26). A large quantity of studies on RIS implantation for NSCLC have been reported with promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Radioactive 125 I seed (RIS) brachytherapy recently has been a standard treatment in early low-to intermediate-risk prostate cancer (16,17). It is a type of low-dose-rate brachytherapy, which could deliver high radiation dose to target tumor while safely sparing the adjacent normal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, this method was used to treat prostate cancer in clinical practice and achieved satisfactory efficacy. 6 To date, this method has been used to treat tumors in multiple systems, including lung cancer and pancreatic cancer. Literature sources have reported that this method can relieve some symptoms and elongate patient survival with satisfactory efficacy.…”
Section: Discussionmentioning
confidence: 99%